Development of Knowledge Management and Enterprise Orientation in Improving Competitive Advantage and Performance at SMEs in West Java - widodo, djoko setyo; Silitonga, P. Eddy Sanusi; Santoso, Edi (International Journal Of Management And Economics Invention, 2021)
The purpose of this study is to analyze is to find, describe, and analyze the development of Knowledge Management and entrepreneurial orientation in increasing competitive advantage and performance in SMEs in West Java. This study uses descriptive and verification methods with the number of analytical observations (research samples) of 200 respondents, who were analyzed by the method of Structural Equation Models (SEM). The results show that Knowledge Management and entrepreneurial orientation have a significant effect on competitive advantage but not on the performance of SMEs in West Java. The results of this research can be useful in the development of management science, especially related to competitive advantage and performance at SMEs through the development of Knowledge Management and entrepreneurial orientation